ASSESSMENT AND PROBLEMS OF DIGITAL READINESS OF MUNICIPALITIES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article examines the assessment and problems of digital readiness of municipalities, where it is important to form a set of indicators to assess the digital readiness of management skills in order to determine the priority areas of digital development of regions. And also to solve the problem of digital readiness of municipalities at the current stage of management.
Keywords: Digital management of socio-economic development, IT market specialists, digital technologies, management process, state and municipal services, level of digital literacy, digital products for the population, level of cybercrime.